2021
DOI: 10.1021/acsami.1c10445
|View full text |Cite
|
Sign up to set email alerts
|

Hitchhiking Nanoparticles: Mesenchymal Stem Cell-Mediated Delivery of Theranostic Nanoparticles

Abstract: Nanotechnology has emerged as a promising solution to permanent elimination of cancer. However, nanoparticles themselves lack specificity to tumors. Due to enhanced migration to tumors, mesenchymal stem cells (MSCs) were suggested as cell-mediated delivery vehicles of nanoparticles. In this study, we have constructed a complex composed of photoluminescent quantum dots (QDs) and a photosensitizer chlorin e6 (Ce6) to obtain multifunctional nanoparticles, combining cancer diagnostic and therapeutic properties. QD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Moreover, it is hypothesized that B cells, [19,30] dendritic cells, [19,30] natural killer cells, [19,44] and platelets [19,45,46] could be a potential source for cell-mediated hitchhiking strategies. Recently, Dapkute et al [47] demonstrated the use of mesenchymal stem cell-driven nanosystems for treating tumors because of their improved migration to the pathological site. This section of the review discusses the application of chemotherapeutic cargo hitchhiked circulatory cells for tumor targeting and treatment.…”
Section: Circulatory Cell-mediated Enhanced Delivery Of Chemotherapeu...mentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, it is hypothesized that B cells, [19,30] dendritic cells, [19,30] natural killer cells, [19,44] and platelets [19,45,46] could be a potential source for cell-mediated hitchhiking strategies. Recently, Dapkute et al [47] demonstrated the use of mesenchymal stem cell-driven nanosystems for treating tumors because of their improved migration to the pathological site. This section of the review discusses the application of chemotherapeutic cargo hitchhiked circulatory cells for tumor targeting and treatment.…”
Section: Circulatory Cell-mediated Enhanced Delivery Of Chemotherapeu...mentioning
confidence: 99%
“…MSCs relocate to regions of tissue injury and inflammation, such as tumors. [19,47] A new category of contrast mediators was based on gold nanocages for in vitro and in vivo surveillance of human MSCs utilizing two-photon imaging and photoacoustic microscopy. [105] Hitchhiking-mediated delivery of fluorescent magnetic nanoparticles (FMNPs) to tumors is an approach utilizing MSCs.…”
Section: Mesenchymal Stem Cells (Mscs) As Biocompatible Hitchhikers T...mentioning
confidence: 99%
See 3 more Smart Citations